The biggest lie on the web: Coming to terms with the failure to read through the lens of the First Amendment. Issue 2 (3rd July 2017) - Sarapin, Susan H.; Morris, Pamela L.; Vo, Ngoc
Abstract: As lines between public and private spaces online continue to blur, contracts are moving closer to the day when government actors will be involved in all of them. When 90%+ of online users do not read the terms-of-service (ToS) agreements of social media sites, they are unaware of possible repercussions of blindly assenting to these unread contracts, including potentially relinquishing a number of their constitutional rights. Primary among these is their First Amendment right to petition the government for relief in a court of law. In most ToSs, the online user must agree to mandatory arbitration in the site owner's venue of choice. Secondary is their sole right to their intellectual property afforded by the Constitution. Through an online survey ( N  = 235), this article reports data concerning respondents' attitudes toward reading ToSs, their demographic information, and their likelihood of accepting a forum-selection term from Twitter, contrary to their potential constitutional rights. Two major findings are that: (a) there was no effect of education on the likelihood of rejecting Google's unfavorable copyright-related terms; and (b) 63.2% of those who state they would not, under any condition, accept the unfavorable Twitter forum-selection term do, indeed, belong to or have belonged to Twitter.